Aplikasi Metodologi OR/MS Dalam Pemodelan Sistem Transportasi Publik Trans Metro Bandung (TMB) Di Kota Bandung - Euis Nina S. Y; V. O. Lawalata (ARIKA, 2010)
This research is arranged to implement the system modeling concept to study public transportation problems in Bandung, East Java, particularly on Trans Metro Bandung program by using OR/MS methodology. Considering to the break event position the results of research through proving an effective loading capacity by defining the number of TMB armada efficiently attribute the contradicting interests of 2 major stakeholders, passengers (customer) and PT. DAMRI Kota Bandung (management). Since the balance position yielded by using 60% of total loading capacity or 6 units the 4 units left is potential to produce profit. Then we conclude the Trans Metro Bandung (TMB) vehicle available now on the number that can create the daily profit. From modeling view, internal validation on model shows that model fulfill the mathematical logic because of its consistency on units and relation patterns between variables.